A 4/8 Subtype α-Conotoxin Vt1.27 Inhibits N-Type Calcium Channels With Potent Anti-Allodynic Effect - Wang, Shuo; Bartels, Peter; Zhao, Cong; Yousuf, Arsalan; Liu, Zhuguo; Yu, Shuo; Bony, Anuja R.; Ma, Xiaoli; Dai, Qin; Sun, Ting; Liu, Na; Yang, Mengke; et al. (Frontiers in Pharmacology, 2022)
A novel 4/8 subtype -conotoxin, Vt1.27 (NCCMFHTCPIDYSRFNC-NH2), was identified from Conus vitulinus in the South China Sea by RACE methods. The peptide was synthesized and structurally characterized. Similar to other -conotoxins that target neuronal nicotinic acetylcholine receptor (nAChR) subtypes, Vt1.27 inhibited the rat 32 nAChR subtype (IC50 = 1160 nM) and was inactive at voltage-gated sodium and potassium channels in rat sensory neurons. However, Vt1.27 inhibited high voltage-activated N-type (CaV2.2) calcium channels expressed in HEK293T cells with an IC50 of 398 nM. An alanine scan of the peptide showed that residues Phe5, Pro9, Ile10, and Ser13 contribute significantly to the inhibitory activity of Vt1.27. The molecular dockings indicate that Vt1.27 inhibits the transmembrane region of CaV2.2, which is different from that of ω-conotoxins. Furthermore, Vt1.27 exhibited potent anti-allodynic effect in rat partial sciatic nerve injury (PNL) and chronic constriction injury (CCI) pain models at 10 nmol/kg level with the intramuscular injection. The pain threshold elevation of Vt1.27 groups was higher than that of α-conotoxin Vc1.1 in CCI rat models. These findings expand our knowledge of targets of -conotoxins and potentially provide a potent, anti-allodynic peptide for the treatment of neuropathic pain.